Autophagy and cancer: taking the ‘toxic’ out of cytotoxics - Giuliani, C.; Dass, Crispin (John Wiley & Sons Ltd., 2013)
Objectives: Autophagy is the catabolic process that facilitates the degradation of proteins and organelles into recyclable nutrients for use by the cell. This article will review current literature to support the hypothesis that autophagy is pivotal in cancer progression and survival and provides some rationale behind the notion that autophagy can be a target for future cancer therapy. Key findings: For the most part, autophagy is pro-cancerous in that it enables the affected cell to meet its nutritional requirements in hypoxic and cytotoxic environments (mainly due to chemotherapy), thus facilitating continued growth and proliferation of tumour cells. As such, it is reasonable to perceive autophagy as a mechanistic target for cancer therapy. However, the challenge to date has been the complexity of the mechanisms involved and the identification of key regulators of autophagy. This has been further complicated by the inherent variation between different cancer cell lines. Summary: Better understanding of the role and mechanisms of autophagy in cancer, with a prelude to ways of exploiting this knowledge, may lead to better chemotherapeutic management of patients suffering from this currently incurable disease.